How does inside information affect sports betting odds? - Karl Whelan (University College Dublin, UCD School of Economics, 2023)
We describe how the presence of insiders with superior information about potential outcomes of sporting events affects odds set by bookmakers, using a generalized version of the model in Shin (1991). The model has been widely cited as an explanation for the pattern of favorite-longshot bias observed in fixed-odds betting markets. We show that disagreement among those bettors without inside information causes favorite-longshot bias. The presence of insiders reduces odds but does not necessarily exacerbate favorite-longshot bias. For realistically calibrated beliefs, the fraction of insiders has a minimal effect on the ratio of favorite to longshot odds and the betting market collapses if this fraction rises above low levels.
Keywords: G14; L83; Z20; 330; Sports Betting; Inside Information